(untitled) (مجلة ديالى للبحوث الانسانية, 2021)
Language learning process builds on prior knowledge and what learners already know about certain topic, including terms and concepts, provides them with a foundation base for moving forwards and construct meaning. Making such connections to the text they are reading increases comprehension and helps them to be metacognitive. Such a process can be best achieved through applying a variety of classroom strategies for activating prior knowledge, or schema, which helps set a stage for new terms, concepts to be presented. Moreover, such strategies would help increase learners’ engagement in classroom activities which involve their participation.